2023
DOI: 10.3390/microorganisms11061571
|View full text |Cite
|
Sign up to set email alerts
|

TGF Beta as a Prognostic Biomarker of COVID-19 Severity in Patients with NAFLD—A Prospective Case–Control Study

Abstract: Non-alcoholic fatty liver disease (NAFLD), the leading cause of chronic liver disease in Western countries, has been identified as a possible risk factor for COVID-19 severity. However, the immunological mechanisms by which NAFLD exacerbates COVID-19 remain unknown. Transforming growth factor-beta 1 (TGF-β1) has an important immunomodulatory and pro-fibrotic role, which has already been described in NAFLD. However, the role of TGF-β1 in COVID-19 remains unclear, and could also be the pathophysiology link betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…They also showed that TGF-β could be used as a predictor of disease fatality, as a higher concentration of this cytokine was found in patients who died than in survivors [20]. A similar positive correlation of TGF-β with the severity of COVID-19 was also found by Susak et al [21]. Opposite results were shown by a group from Serbia: in their study, deceased patients had significantly lower TGF-β concentrations than survivors.…”
Section: Discussionsupporting
confidence: 56%
“…They also showed that TGF-β could be used as a predictor of disease fatality, as a higher concentration of this cytokine was found in patients who died than in survivors [20]. A similar positive correlation of TGF-β with the severity of COVID-19 was also found by Susak et al [21]. Opposite results were shown by a group from Serbia: in their study, deceased patients had significantly lower TGF-β concentrations than survivors.…”
Section: Discussionsupporting
confidence: 56%
“…We can hypothesize that patients with SLD might respond differently to infections, which could influence their outcomes. This has recently been suggested in COVID-19, where patients with SLD had distinct cytokine profiles that were associated with adverse outcomes [45,46].…”
Section: Discussionmentioning
confidence: 78%
“…It has been suggested that blood levels of TGF-β in patients with non-alcoholic fatty liver disease may be an effective biomarker of coronavirus disease 2019 (COVID-19) severity and adverse outcomes [ 66 ]. It has also been suggested that TGF-β blockade should be used to treat COVID-19 [ 67 ].…”
Section: Discussionmentioning
confidence: 99%